Comparison of Management of Finnish Education Units with Indonesia - Iman; Yusuf; Rizky Maulana Yusali; Syahruna Mubarokah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Education is an important factor in human development. The education system in each country is different, depending on the existing social, cultural, political and economic context. Finland is known as one of the countries that has a quality and successful education system that is recognized worldwide. Indonesia, as a developing country, is still trying to improve the quality of education that can meet the needs and challenges of the times. This research aims to compare the management of educational units in Finland and Indonesia, using descriptive qualitative methods. Data was collected from various literature sources relevant to the research topic. The research results show that there are several differences between the management of educational units in Finland and Indonesia, namely: (1) Finland applies the principle of equality, while Indonesia colors its education system with a lot of competition; (2) Finland does not have a class failure and student ranking system, while Indonesia still uses this system; (3) Finland provides a weekly study load of around 30 hours, while Indonesia provides around 40 hours; (4) Finland places more emphasis on problem solving methods, while Indonesia places more emphasis on learning in class; (5) Finland does not burden students with many assignments, whereas Indonesia almost makes assignments a routine agenda for every meeting; (6) Finland sets a minimum teacher qualification of S2 (Master), while Indonesia is D4; (7) Finland sets the minimum qualification for students entering basic education at a minimum of 7 years, while Indonesia's minimum is 6 years (5.5 years with a written recommendation from a professional psychologist). It is hoped that this research will provide insight and inspiration for education managers and practitioners in Indonesia to continue to innovate and improve the quality of education.